Kajian Pengawasan Stone Quarry Mining oleh Pemerintah Kabupaten Enrekang - Zainal Zainal; Muhammad Sabir; Khaerul Mannan; Kairuddin Kairuddin; Saharuddin Saharuddin (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
This study aims to determine and analyze the authority of the Regency/City Government in supervising rock mining activities and the factors influencing the Enrekang Regency Government's supervision of rock mining. This study employs empirical research methods, using a legislative and social approach. Data sources include primary and secondary data. Data analysis will be conducted using an observational-sensory and theoretical-rational approach, employing a reasoning model that first utilizes inductive logic and then deductive logic. The result of this study indicate that the Enrekang Regency Government's authority in supervising rock mining is limited. This is influenced by the provisions of Law Number 23 of 2014 concerning Regional Government and Law Number 3 of 2020 concerning Minerals and Coal, which devolve licensing and enforcement authority to the provincial and central levels. The Regency Government's role is limited to technical supervision, guidance, outreach, and the implementation of Regional Regulations. In addition, there are several factors that influence weak supervision, namely: limited regulations and authority, limited human resources and budget, low public awareness of the importance of environmental permits and documents, economic dependence of the community on mining, weak regional political commitment, minimal socialization, lack of consistent field supervision, and ineffective implementation of Regional Regulations.